ON THE WAY TO THE ECO-MODERNIZATION OF RUSSIA (REFLECTING ON THE BOOK YANICKII O.N. ECO-MODERNIZATION OF RUSSIA: THEORY, PRACTICE, PERSPECTIVES - G. M. Abdurakhmanov; M. N. Ivanov; G. E. Kudinova; G. S. Rosenberg (Юг России: экология, развитие, 2014)
The article discusses various aspects of eco-modernization ofRussia, presented in the monograph of Yanitsky. Objectives of environmental-ecological modernization is the change of the state environmental policy to achieve, at least, three main results: im-provement of quality of life, increase of economic efficiency and ensure a «green growth» of the economy and energy, and the conservation and restoration of the natural environment.